2001
DOI: 10.1177/112070000101100106
|View full text |Cite
|
Sign up to set email alerts
|

Drainage versus Non-Drainage in Total Hip Arthroplasty. A Prospective Randomised Study

Abstract: We present a prospective review of 23 patients having 25 primary total hip arthroplasties (THAs) over a two-month period. Patients were randomly allocated into two groups, one with wound drainage and the other without. There were 12 hips in the Drain group and 13 hips in the No-drain group. Demographic characteristics and risk factors were similar in the two groups. The average wound score (ASEPSIS) was found to be higher for the No-drain group and this was statistically significant. In the No-drain group, 7 o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0
4

Year Published

2001
2001
2013
2013

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 13 publications
0
17
0
4
Order By: Relevance
“…On the other hand, Waugh [21] showed a 1% infection rate in the wounds treated with suction as compared with the 3% infection rate in the control group. Finally, Ravikumar [17] abruptly stopped his study after having a 54% infection rate for the non-drained group compared to 8% in the drained group. In the present study, no superWcial and no deep infections were encountered.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, Waugh [21] showed a 1% infection rate in the wounds treated with suction as compared with the 3% infection rate in the control group. Finally, Ravikumar [17] abruptly stopped his study after having a 54% infection rate for the non-drained group compared to 8% in the drained group. In the present study, no superWcial and no deep infections were encountered.…”
Section: Discussionmentioning
confidence: 99%
“…Results of clinical trials on the use of drains are conXicting and most of them include diVerent surgical procedures into the same study [3,7,20], have a short follow-up [4,12,18] or use small numbers [12,17].…”
Section: Introductionmentioning
confidence: 99%
“…Following the search strategy outlined above, and the inclusion and exclusion criteria, the two independent reviewers located 20 RCTs [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22] involving 3,186 patients for our analysis ( Table 2). The entire process is shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Eight studies [3,9,13,17,19,20,22] reported data on postoperative pain. And two of them [11,19] reported that more patients experienced mid-thigh pain in the no-drainage group than in the drainage group, while six [3,9,13,17,20,22] reported no significant difference. Based on the data pooled from Dora et al [17] and Kleinert et al [20], no significant difference of pain could be found between the groups (WMD, −0.09 [95 % CI, −0.63 to 0.44]; p=0.73).…”
Section: Functional Assessment and Painmentioning
confidence: 98%
See 1 more Smart Citation